Transgressive Truths and Flattering Lies The Poetics and Ethics of Anglophone Arab Representations - Schmitz, Markus (Postcolonial Studies, 2020)
This book explores the formative correlations and inventive transmissions of Anglophone Arab representations ranging from early 20th century Mahjar writings to contemporary transnational Palestinian resistance art. Tracing multiple beginnings and seminal intertexts, the comparative study of dissonant truth-making presents critical readings in which the notion of cross-cultural translation gets displaced and strategic unreliability, representational opacity, or matters of act advance to essential qualities of the discussed works' aesthetic devices and ethical concerns. Questioning conventional interpretive approaches, Markus Schmitz shows what Anglophone Arab studies are and what they can become from a radically decentered relational point of view. Among the writers and artists discussed are such diverse figures as Rabih Alameddine, William Blatty, Kahlil Gibran, Ihab Hassan, Jabra Ibrahim Jabra, Emily Jacir, Walid Raad, Ameen Rihani, Edward Said, Larissa Sansour, and Raja Shehadeh.